PENGARUH GREEN MARKETING, SOSIAL MEDIA MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOTOR HONDA MATIC DI ASTRA MOTOR CABANG CILEGON - Saripudin Saputra; Andi Hasryningsih Asfar (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to examine the effect of green marketing, social media marketing and brand image on purchasing decisions of automatic Honda motorcycles at PT Astra Motor Cilegon branch and examine the effect of green marketing, social media marketing and brand image simultaneously on purchasing decisions of automatic Honda motorcycles in PT Astra Motor Cilegon branch.The method used in this study was a quantitative method, the sample used was 73 respondents, the number of samples was determined using purposive sampling, the data analysis technique used multiple linear regression with the help of the SPSS program. Based on the partial test (t-test) the results of this study state that the green marketing variable influences the decision to purchase an automatic Honda motorbike at PT Astra Motor Cilegon branch. Likewise for the social media marketing variable that influences the decision to purchase an automatic Honda motorbike at PT Astra Motor Cilegon branch. The brand image variable also influences the decision to buy an automatic Honda motorbike at PT Astra Motor Cilegon branch. Simultaneously the variables Green marketing, social media marketing and brand image influence the decision to purchase an automatic Honda motorbike at PT Astra Motor Cilegon branch